Inhibition of Signal Transducer and Activator of Transcription 3 (STAT3) reduces neonatal hypoxic‐ischaemic brain damage. Issue 5 (11th January 2016) - Hristova, Mariya; Rocha‐Ferreira, Eridan; Fontana, Xavier; Thei, Laura; Buckle, Rheanan; Christou, Melina; Hompoonsup, Supanida; Gostelow, Naomi; Raivich, Gennadij; Peebles, Donald
Abstract: Hypoxic‐ischaemic encephalopathy is a leading cause of child death, with high mortality and morbidity, including cerebral palsy, epilepsy and cognitive disabilities. Hypoxia‐ischaemia (HI) strongly up‐regulates Signal Transducer and Activator of Transcription 3 (STAT3) in the immature brain. Our aim was to establish whether STAT3 up‐regulation is associated with neonatal HI‐brain damage and evaluate the phosphorylated STAT3‐contribution from different cell types in eliciting damage. We subjected postnatal day seven mice to unilateral carotid artery ligation followed by 60 min hypoxia. Neuronal STAT3‐deletion reduced cell death, tissue loss, microglial and astroglial activation in all brain regions. Astroglia‐specific STAT3‐deletion also reduced cell death, tissue loss and microglial activation, although not as strongly as the deletion in neurons. Systemic pre‐insult STAT3‐blockade at tyrosine 705 (Y705) with JAK2‐inhibitor WP1066 reduced microglial and astroglial activation to a more moderate degree, but in a pattern similar to the one produced by the cell‐specific deletions. Our results suggest that STAT3 is a crucial factor in neonatal HI‐brain damage and its removal in neurons or astrocytes, and, to some extent, inhibition of its phosphorylation via JAK2‐blockade reduces inflammation and tissue loss. Overall, the protective effects of STAT3 inactivation make it a possible target for a therapeutic strategy in neonatal HI. Current data show that neuronal and astroglial STAT3 molecules are involved in the pathways underlying cell death, tissue loss and gliosis following neonatal hypoxia‐ischaemia, but differ with respect to the target of their effect. Y705‐phosphorylation contributes to hypoxic‐ischaemic histopathology. Protective effects of STAT3 inactivation make it a possible target for a therapeutic strategy in neonatal hypoxia‐ischaemia. Abstract : Current data show that neuronal and astroglial STAT3 molecules are involved in the pathways underlying cell death, tissue loss and gliosis following neonatal hypoxia‐ischaemia, but differ with respect to the target of their effect. Y705‐phosphorylation contributes to hypoxic‐ischaemic histopathology. Protective effects of STAT3 inactivation make it a possible target for a therapeutic strategy in neonatal hypoxia‐ischaemia.